Pilot Feasibility Study of Incorporating Whole Person Care Health Coaching Into an Employee Wellness Program - Nelson, Anna; Moses, Olivia; Rea, Brenda; Morton, Kelly; Shih, Wendy; Alramadhan, Fatimah; Singh, Pramil N. (Frontiers in Public Health, 2021)
Prior research supports positive health coaching outcomes, but there is limited literature on the integration of employer-sponsored health coaching into employee wellness strategy. The aim of our mixed methods study was to assess feasibility, acceptability, and preliminary efficacy of incorporating a whole-person care model of health coaching into an employee wellness program (i.e. weight loss, smoking cessation) that is made available by an employer-sponsored health plan. For the quantitative study, eligible employees and covered spouses (n=39) from Loma Linda University Health were recruited into a novel, 12-week, whole person care intervention that combined health coaching and health education and examined outcomes from surveys detailing the participants’ experience and biometric data from the intervention and maintenance periods. For the qualitative study, data were collected through key informant interviews from three health coaches and six intervention participants who were recruited via random sampling. Health coaching was well received by the participants, and led to a slight albeit positive behavioral change for obesity. A significant decrease in body mass index occurred over 12 weeks of intervention (-0.36 kg/m2, p=0.016), that did not continue during the maintenance phase (-0.17 kg/m2, p=0.218). Qualitative findings indicated improved personal health awareness, accountability, motivation, and self-efficacy along with goal setting and barrier overcoming skills among the key themes. Our pilot study findings identify positive behavior change effects of an employee health intervention based on a whole person care model of health coaching with integrated health education, and also identify the need for methods to maintain behavior change (i.e., mHealth, peer-support) post-intervention. Further investigation in randomized controlled trials is the next step in this research.